Adapting long-lived investments under climate change uncertainty - Klaus Eisenack; Marius Paschen (Journal of Environmental Economics and Management, 2022)
Does climate change adaptation require that investments are designed to be more robust? What about when climate change is more uncertain? What if the climate changes faster? This decision problem is difficult if the design of the investments is irreversible for their lifetime, for instance, in the construction industry. We study an irreversible design decision when the investment starts, combined with an irreversible option to abandon. The design determines the investment's robustness to sustain detrimental conditions. We find that for short-lived investments, optimal robustness decreases if the climate changes faster, and increases if uncertainty is higher. For long-lived investments, these effects reverse. This has implications for decision makers who plan infrastructure adaptation, for instance, that adverse climate change does not require more robust investments under the identified circumstances.
Keywords: C61; D25; D81; Q54; 330; Irreversibility; Lifetime; Optimal stopping; Robustness; Stochastic dynamic control